Self-efficacy and social behavior of higher school students: socio-psychological aspects (The Journal of Psychology and Sociology, 2021)
The article is dedicated to the current topic-the behavior of high school students in different life situations. The purpose of this article is to study the relationship between the degree of harmony of the individual, and the characteristics of subjectivity, and the self-efficacy of the students. Authors interpret self-effectiveness as the concept of assessing their own behavior. It should be noted that the ability to control his or her actions, or not, of confidence or doubt in their own abilities, they are organically linked    to the state of a person and his or her loci, as well as the personal characteristics of the individual, the peculiarities of the perception and analysis of the situation, the nature of the adaptive behavior, the level  of harmony of the individual. The studies were conducted, which is shown to have a direct connection between the elements of the personality of the harmony with the characteristics of subjectivity, and the student’s personal performance indicator. In this study, the authors point out that, regardless of their age, and in order to meet your own abilities, you need to understand the way in which it is located, it should     be possible for a person to select the choices that are necessary for a particular view. Regardless of the   age, to understand the skills a person needs to understand the situation in which they are located, and     if you are used to, and you can select the exact ways on how to solve it, which is a necessary and very important.Key words: human qualities, human behavior, society, student youth, self–efficacy, harmonious personality, subjectivity.